2020
DOI: 10.1055/s-0040-1715899
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor-Independent Coagulation Correlates with Clinical Phenotype in Factor XI Deficiency and Replacement Therapy

Abstract: Background In factor XI (FXI) deficiency, bleeding cannot be predicted by routine analyses. Since FXI is involved in tissue factor (TF)-independent propagation loop of coagulation, we hypothesized that investigating the spatiotemporal separated phases of coagulation (TF-dependent and -independent) could improve diagnostics. Objectives This article investigates the correlation of parameters describing TF-dependent and -independent coagulation with the clinical phenotype of FXI deficiency and their abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Global TG assays have been used to assess hemostatic potential after FXI replacement with FXI concentrates. 44,57,58 In general, these studies showed that after in vitro spiking of FXI-deficient plasma or after infusion of FXI concentrate in patients, TG was improved. Of note, after the infusion of FXI concentrate, TF-independent parameters measured ex vivo by TD assay shifted toward hypercoagulation at levels of FXI of about 30%.…”
Section: Global Assay For Monitoring Fxi Replacementmentioning
confidence: 97%
See 4 more Smart Citations
“…Global TG assays have been used to assess hemostatic potential after FXI replacement with FXI concentrates. 44,57,58 In general, these studies showed that after in vitro spiking of FXI-deficient plasma or after infusion of FXI concentrate in patients, TG was improved. Of note, after the infusion of FXI concentrate, TF-independent parameters measured ex vivo by TD assay shifted toward hypercoagulation at levels of FXI of about 30%.…”
Section: Global Assay For Monitoring Fxi Replacementmentioning
confidence: 97%
“…TF þ , presence of tissue factor; TF À , absence of tissue factor. cohort of 24 FXI-deficient individuals, Bertaggia Calderara et al 44 could observed that FXI-deficient bleeders were characterized by a significant lower TG and clot formation rate in the TF-independent phase of coagulation. An algorithm based on combinatorial ROC analysis of TG and fibrin clot formation parameters could identify all of the FXI-deficient patients with bleeding phenotype and 82% of FXI patients without bleeding symptoms.…”
Section: Clot Formation and Fibrinolysis Assaymentioning
confidence: 99%
See 3 more Smart Citations